Practical .NET for Financial Markets - Shetty, Yogesh; Jayaswal, Samir; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
This unique book examines up-to-the-minute uses of technology in financial markets and then explains how you can profit from that knowledge. To participate in mainstream .NET development, you must address the changes in financial markets by using the most sophisticated tools available, Microsoft .NET technology. Software developers and architects, IT pros, and tech-savvy business users alike will find this book comprehensive and relevant. Each chapter presents problems and solutions that cover business aspects and relevant .NET features. Each aspect of .NET is analyzed in its proper context, so you'll understand why it is relevant and applicable in a real-life business case.
Introducing the Equities Market -- The Order-Matching Engine -- The Data Conversion Engine -- The Broadcast Engine -- The Application Operation Engine -- STP Security -- STP Interoperability -- Equity Arbitrage -- .NET 2.0.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books